The challenges of a small population exposed to multiple anthropogenic stressors and a changing climate: the St. Lawrence Estuary beluga - Lesage, Véronique (Polar research, 2021)
Until 2012, the St. Lawrence Estuary beluga population was considered stable with about 1100 individuals. An abnormally high number of calves reported dead that year triggered a population status reassessment. This review article summarizes the findings from this reassessment and various studies subsequent to it and provides an updated analysis of carcass recovery rates up to 2019. The 2013 review indicated a decreased incidence of cancer in adults, suggesting positive impacts from the regulation of toxic substances (e.g., PCBs and PAHs). However, the review also revealed that the population initiated a decline of ca. 1% per year in the early 2000s and had reached a size of ca. 900 individuals by 2012. This decline was accompanied by high inter-annual variability in calf survival and pregnancy rates and by more frequent peripartum complications among dead females. The change in population dynamics coincided with a shift in the St. Lawrence ecosystem structure and warmer environmental conditions, suggesting a link through effects on reproductive success and adult female body condition. This was supported by the continued high calf mortality after 2012 and a documented decline of fat reserves in beluga blubber from 1998 to 2016. Other factors, such as the exposure to chronic vessel noise, increasing whale-watching activities, high contaminant levels and episodic harmful algal blooms, may also be contributing to the long-term non-recovery and current decline of the population. The strong natal philopatry and complex social system of the beluga likely increase its vulnerability to extinction risk by limiting dispersal.